Two-stage treatment of an unusual haemobilia caused by intrahepatic pseudoaneurysm - Takeda, Kazuhisa (Baishideng Publishing Group Co., Limited, 2010)
A 84-year-old man with a surgical history of subtotal gastrectomy for gastric cancer was transferred to our department because of a disorder of consciousness. Septic shock due to obstructive suppurative cholangitis secondary to choledocholithiasis was diagnosed. Anemia was also present, and upper gastrointestinal tract endoscopy revealed blood emerging from the Papilla of Vater. The cause of the anemia was identified as haemobilia. Angiography showed a small aneurysm over the artery on segment 3 (A3). The cause of the haemobilia was suspected to be the bleeding into the biliary tree from this aneurysm. Because the patient’s general condition was poor, minimally invasive therapy was needed. Transcatheter arterial embolization (TAE) was selected initally. Later, lateral sectionectomy was performed in order to remove the aneurysm on A3. No surgical complication occurred and, after surgery, no haemobilia was identified. In conclusion, a two-stage treatment, namely, surgery following TAE, is recommended for patients in a physically poor condition who have haemobilia due to intrahepatic aneurysm.